Justice In Limbo: Missing Court Records In Malawi - Gumboh, Esther (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The right to a fair trial includes the right to be tried within a reasonable time and to appeal. Missing court records delay the criminal process and create significant challenges for offenders who wish to exercise their right to appeal. Through case analysis, this contribution argues that Malawi’s response to missing court records translates into an incoherent and inconsistent approach that undermines the right to a fair trial, often leaving accused persons in limbo. While the Judiciary has made some headway in responding to missing court records, the existing jurisprudence does not adequately protect the rights of accused persons. A legislative response is recommended to ensure consistency and certainty. In the meantime, the Judiciary must proactively develop guidelines to govern the handling of cases with missing files.